BUSINESS PROPOSAL TRAINING AS A MEANS OF DEVELOPING BUSINESS IDEAS FOR STIE WIKARA STUDENTS - Rhiswandi, Rhandi (Jurnal Pengabdian dan Kewirausahaan, 2026)
Business proposal training is a community service activity that aims to improve students' ability to understand the basics of preparing a business plan from the beginning of lectures. This activity was held at STIE Wikara Purwakarta with 18 participants in the 1st semester night class (1WM03) of the Management Study Program. The training is focused on the introduction of concepts and the preparation of business proposal drafts which include aspects of business methods, literature review, marketing strategies, financial planning, operations, and human resource management. The implementation method includes interactive lectures, group simulations, and direct assistance in compiling a systematic business proposal structure. The results of the activity show an increase in students' understanding of the stages of business planning and the ability to integrate management theory into the practice of preparing proposals. This training is expected to be the first step in fostering entrepreneurial interest and economic independence of STIE Wikara students.